2022
DOI: 10.1200/jco.21.01885
|View full text |Cite
|
Sign up to set email alerts
|

Minority Enrollment in Phase II and III Clinical Trials in Urologic Oncology

Abstract: PURPOSE Proportionate minority representation in clinical trials is an important step toward addressing health care inequities. Given the paucity of data on this topic in urologic oncology, we sought to quantify the enrollment of minority patients in clinical trials studying prostate, kidney, and bladder/urothelial cancers. METHODS The ClincialTrials.gov database was queried for completed phase II and III interventional trials in prostate, kidney, and bladder cancers. The SEER database was used to calculate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Inclusion of patients from racial and ethnic minority groups in phase 1 cancer trials was worse than observed in phase 3 trials, especially among Black participants (−6.9% difference in Black participants in phase 1 trials in 2012-2018 compared with −2.6% difference in phase 3 trials since year 2011). 4,9 Similar disparities in phase 1 cancer clinical trial enrollment have been noted in studies conducted at single institutions. 10 When examining racial and ethnic disparities in clinical research, it is essential to acknowledge the harms that individuals of racial and ethnic minority groups have experienced at the hands of the US health care system, especially in the research setting.…”
Section: Discussionmentioning
confidence: 62%
“…Inclusion of patients from racial and ethnic minority groups in phase 1 cancer trials was worse than observed in phase 3 trials, especially among Black participants (−6.9% difference in Black participants in phase 1 trials in 2012-2018 compared with −2.6% difference in phase 3 trials since year 2011). 4,9 Similar disparities in phase 1 cancer clinical trial enrollment have been noted in studies conducted at single institutions. 10 When examining racial and ethnic disparities in clinical research, it is essential to acknowledge the harms that individuals of racial and ethnic minority groups have experienced at the hands of the US health care system, especially in the research setting.…”
Section: Discussionmentioning
confidence: 62%
“…However, this study reported that only 4% of participants were non-Hispanic Black men, which limits the external validity of the findings. 40 This is in the context of other studies that have shown that, when compared with white patients, Black patients in the US are more likely to have a larger tumour volume, 41 elevated in itial PSA levels, 42 longer time intervals between screenings 43 and earlier transformation to clinically important disease. 18,19 If Black people have been shown to present with more aggressive and advanced disease in PSA-eligible populations, applying averagerisk guidelines to this population ignores their lived reality.…”
Section: Should Black People In Canada Be Screened Differently For Pr...mentioning
confidence: 77%
“…Clinical trials of prostate cancer screening and treatment have not adequately included Black participants. 39,40 Both the CUA and USPSTF guidelines on prostate cancer refer to data from the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. However, this study reported that only 4% of participants were non-Hispanic Black men, which limits the external validity of the findings.…”
Section: Should Black People In Canada Be Screened Differently For Pr...mentioning
confidence: 99%
“…Les essais cliniques sur le dépistage et le traitement du cancer de la prostate n'ont pas inclus suffisamment de participants noirs 39,40 . Les lignes directrices de l'AUC et du USPSTF sur le cancer de la prostate font référence à des données tirées de l'étude Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial.…”
Section: Les Canadiens Noirs Devraient-ils Avoir Accès à Un Dépistage...unclassified
“…Les lignes directrices de l'AUC et du USPSTF sur le cancer de la prostate font référence à des données tirées de l'étude Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. Or, cette étude a révélé que seulement 4 % des participants étaient des hommes noirs non hispaniques, ce qui limite la validité externe de ses conclusions 40 . Et elle se situe dans un contexte où d'autres études ont montré que, comparativement aux patients blancs, les patients noirs aux États-Unis sont plus susceptibles de présenter une tumeur plus volumineuse 41 , des taux initiaux d'APS élevés 42 , des contrôles plus espacés 43 et une évolution plus précoce en maladie cliniquement importante 18,19 .…”
Section: Les Canadiens Noirs Devraient-ils Avoir Accès à Un Dépistage...unclassified